Single/three-phase symmetrical bipolar voltage multipliers for X-ray power supply - Shahid, Iqbal; Rosli, Besar; C., Venkataseshaiah (2008)
This paper presents a bipolar symmetrical Cockcroft-Walton voltage multiplier (VM) for X-ray power supply. The proposed bipolar symmetrical VM is formed by connecting positive and negative symmetrical VMs consisting of equal number of stages in parallel to ac driving voltage sources. It has better output voltage regulation and faster dynamic response as compared to conventional symmetrical VM. Its bipolar structure cancels the fundamental and higher order odd harmonics of ripples caused by any asymmetry of driving voltage. The bipolar approach is further extended to previously proposed three-phase voltage multiplier topology with significant improvement in dynamic response and voltage regulation. The experimental and simulation results are presented to support the claim of proposed technique.